Growth characteristics and copper accumulation of bacterial consortium Acinetobacter sp. and Cupriavidus sp. isolated from a wastewater treatment plant - WAHYU IRAWATI; TRIWIBOWO YUWONO; NOMMENSEN PANGIHUTAN OMPUSUNGGU (Society for Indonesian Biodiversity, 2018)
Irawati W, Yuwono T, Ompusunggu NP. 2018. Growth characteristics and copper accumulation of bacterial consortium Acinetobacter sp. and Cupriavidus sp. isolated from a wastewater treatment plant. Biodiversitas 19: 1884-1890. Pollutant treatments are part of the human calling, as the crown of creation, to subdue, preserve, and cultivate the earth in bringing goodness for all creatures. Bioremediation of copper using indigenous bacteria is well known as the best water treatment for polluted environment recovery. Acinetobacter sp. and Cupriavidus sp. are indigenous bacteria isolated from industrial sewage in Indonesia. Bioremediation in environment is a process involving community of bacterial consortium for heavy metal or any other polluting materials accumulation. The purposes of this research were: (i) to characterize growth of Acinetobacter sp. and Cupriavidus sp. consortia in sewage medium, enrichment medium, and medium supplemented with copper, (ii) to establish the potency of bacterial consortia to accumulate copper. The growth of bacteria was observed based on cell turbidity using spectrophotometer at wavelength of 600 nm. Cells pellet was destructed by nitric acid at 100oC and copper concentration was analyzed by atomic absorption spectrophotometer as copper accumulation value. The results showed that the growth of bacterial consortia in medium containing copper was better than that of single bacterium. The best bacterial consortium was the mixture of Acinetobacter sp. IrC1 and Acinetobacter sp. IrC2. The use of sewage as cultivation medium decreased bacterial growth by up to 25% but still resulted in the same level of logarithmic phase in enrichment medium. The highest accumulation capability was of a consortium of Acinetobacter sp. IrC1 and Acinetobacter sp. IrC2 at a level of 6.45 g/mg copper/g cells dry weight, suggesting that 5.09% of copper were accumulated by cells. It was concluded that the best composition of consortia in growth and copper accumulation capability was the mixture of Acinetobacter sp. IrC1 and Acinetobacter sp. IrC2. These results may be due to the fact that both bacteria belong to the same genus that allowed them for synergistic interactions.